Mobile GCS를 이용한 Network RTK 기반 경계 복원 측량 드론 - 정은지(Eun-ji Jeong); 장민석(Min-seok Jang); 이연식(Yon-sik Lee) (한국정보통신학회논문지, 2021)
The cadastre in Korea was established with the outdated technology of the Japanese colonial period, and thus currently 15% of the Korea domestic land does not match the cadastral map. Accordingly, the government has been establishing the Korean cadastre under the name of 'Cadastral Re-investigation Project' and is changing the origin of the survey to the world geodetic system. Assuming that the project is completed, we propose a drone boundary survey method that can be used to easily survey using the exact digital cadastral information. The developed mobile GCS application can control the drone and acquire the boundary point coordinates recorded in the cadastre, and the drone automatically flies to mark the boundary points. The developed prototype of drone made a tour along the 6 boundary points in 2 minutes. 우리나라 토지공부는 일제 시대의 낙후된 기술로 정립되어 현재 국내 토지의 15%가 지적도와 맞지 않는다. 이에 정부는 '지적재조사 사업'이라는 이름 아래 우리나라 토지공부를 정립하고 측량 원점을 세계측지계로 변경 중에 있다. 지적재조사 사업이 끝난 후 우리나라 디지털 정보 서비스가 구축되어 디지털 지적정보가 제공될 때, 그 정보를 이용하여 손쉽게 측량할 수 있는 드론 경계 복원 측량 방법을 제안한다. Mobile GCS는 모바일 어플로 드론을 제어하고 토지공부에 기록된 경계점 좌표를 획득하여 드론이 자동 비행하여 경계점을 표시하도록 한다. 개발한 프로토타입 드론으로 6개 경계점을 2분 내로 순회하였다.